Understanding the Role of Bystanders and Peer Support in School Bullying - Helen Cowie (International Journal of Emotional Education, 2014)
Research into school bullying has traditionally focussed on the actual protagonists – the perpetrators and the targets. Consequently, we know a great deal about the psychological characteristics of bullies and victims and the consequences of bullying in undermining the emotional well-being of both targets and perpetrators. While an understanding of the personal aspects of the bully-victim relationship is important, it only addresses part of the issue. Bullying is experienced within a group of peers who adopt different participant roles and who experience a range of emotions. In this article, I argue that bullies do not act alone but rely on reinforcement from their immediate group of friends as well as the tacit approval of the onlookers. This article explores the conflicting emotions often experienced by the bystanders. It also makes some suggestions about interventions to empower bystanders to take action against bullying through, for example, such interventions as peer support.